STRUCTURAL METAPHOR OF LOVE IN ENGLISH SONGS IN THE LATE 20TH CENTURY FROM STYLISTIC AND COGNITIVE PERSPECTIVES - Nguyen Thi Hong Thu (Journal of Applied Linguistics and Literature)
Metaphor is a powerful linguistic device for musicians to write love songs. Through love songs, metaphor is understood and studied more interestingly and effectively. The paper identified distinctive linguistic features of metaphors as well as interpreted the metaphorical images of love in the songs. The data for analysis are the samples randomly taken from English love songs in the late 20th century. There are 68 songs used with 80 verses included in the corpus for analysis. All the collected data were qualitatively and quantitatively processed. In this paper, the metaphorical images in the songs were classified into three different kinds, namely structural metaphors, ontological metaphor, and orientational metaphors, of which the number of structural one ranks the first. The writer analyzed 46 structural metaphors to find out conceptual meaning transference from the vehicles to the tenors from cognitive perspectives and the rhetorical value distributed to songs from stylistic perspectives. Finally, the implication for learning, teaching and translating metaphor was presented.